Enhancing customer satisfaction through digital banking: A structural equation model approach - Thapaliya, Prithivi Raman; Maharjan, Purna Narayan; Adhikari, Shukra Raj; Padal, Pushpa Raj; Dongol, Padam; Tandukar, Siddhartha (Edelweiss Applied Science and Technology, 2026)
The rapid expansion of digital banking has transformed the traditional banking landscape, positioning customer satisfaction at the center of competitive strategy. This study examines how digital banking improves customer satisfaction in the Nepalese banking industry. The research employed a quantitative method and collected primary data from 388 customers of three selected commercial banks in Kathmandu Valley. After data collection, Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to assess the relationships among variables. The results indicate that all five dimensions, efficiency, privacy, reliability, responsiveness, and cost-effectiveness, have significant and positive effects on customer satisfaction. Among these, responsiveness emerges as the strongest predictor, showing a significant impact on customer satisfaction. This study contributes to the developing literature on digital banking in developing countries by examining the influence of technology-based banking experiences on consumer perceptions and satisfaction. It offers valuable guidance for bank leaders and policymakers aiming to develop and implement customer-focused digital strategies. By improving key dimensions of digital banking quality, financial institutions can gain a competitive edge and foster lasting customer satisfaction.